A Pilot Study to Develop the Rapid Estimate of Adult Literacy in Audiology - Hua Ou (SLACK Incorporated, 2022)
Background: Health literacy describes an individuals' ability to maximize their potential in health care, including one's ability to understand information needed to make informed health decisions. A variety of general and condition-specific health literacy assessment tools have been created to help health professionals assess patients' health literacy skills and tailor the need for health care communication or education; however, there are no such tools available for the audiology field. Objective: The purpose of the study was to develop an objective reading recognition audiology-related health literacy assessment tool, the Rapid Estimate of Adult Literacy in Audiology (REALA). Methods: This was a cross-sectional study (N = 200). The initial version of the REALA contained 99 words specifically related to audiology. The final version, revised to have improved clinical utility, contained a total of 48 words that were selected based on item difficulty, item discrimination score, and point-biserial index using classical item analysis. Key Results: The total pass rate for the final version of the 48-word REALA was 0.72 (standard deviation = 0.45) and the Cronbach coefficient alpha was 0.93. Once the comprehension component is added to the tool, the REALA can be a valuable health literacy assessment tool that health professionals use to evaluate patients' audiology-related health literacy. Conclusion: Once the comprehension component is added to the tool, the REALA can be a valuable health literacy assessment tool that health professionals use to evaluate patients' audiology-related health literacy. [HLRP: Health Literacy Research and Practice. 2022;6(2):e88-e95.] Plain Language Summary: A health literacy assessment tool, the REALA, was developed in the study. The final version of REALA contained 48 words relative to hearing healthcare. The results suggested that REALA can help health professionals assess patients' hearing related health literacy and tailor the need for hearing health care communication or education.